Silicon Germanium Heterojunction Bipolar Transistor for Digital Application - Engelin Shintadewi Julian (Institute of Advanced Engineering and Science, 2012)
Bipolar transistor performances can be characterized by figures of merit such as cutoff frequency, maximum frequency of oscillation and ECL gate delay. We studied the required figures of merit for digital application and the effects of lateral and vertical scaling to the figures of merit of SiGe HBT. With lateral scaling, the width of emitter finger is scaled down from 0.25 to 0.12 ?m while with the vertical scaling, the base width is scaled down to reduce the base delay. We also observed the effects of Ge profile and Ge fraction to the devices performances. Bipole3 5.3.1G is used to help us in the study. We found that high frequency cutoff and maximum frequency of oscillation as well as low ECL gate delay are all important for digital applications. Scaling down the emitter finger width enhanced the maximum frequency of oscillation and reduced ECL gate delay significantly while scaling down the base width increased the cutoff frequency and current gain. DOI: http://dx.doi.org/10.11591/telkomnika.v10i3.609